Edukasi Penggunaan Kontrasepsi IUD (Intra Uterine Device) Dengan Service Excelent Guna Meningkatkan Pengetahuan Kesehatan Reproduksi Pada Pasangan Usia Subur Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deliserdang Tahun 2023 - Dewi Sartika Hutabarat; Retno Wahyuni; Edi Subroto; Oktaviani Zebua; Yesika Harahap; Cristoboy Vasius (BADAN PENERBIT STIEPARI PRESS, 2023)
Communication, Information and Education (IEC) is a process of delivering messages of exchange of thoughts or information in order to create a sense of mutual understanding and mutual trust for the realization of a good relationship between one person and another. In addition, it can positively influence public health behavior, by using various principles and methods of communication, both using interpersonal communication and mass communication. This is influenced by the limited contraceptive options available, the fear of experiencing side effects, knowledge, attitudes and actions. The purpose of this study was to analyze the effect of the effectiveness of Communication, Information and Education (KIE) with the lecture method and leaflet media on the decision making of Fertility Couples (PUS) in choosing contraceptives in the working area of Bangun Rejo village , Tanjung Morawa sub-district. This type of research uses a quasi-experimental with re-treatment design (Pretest and Posttest Group Design), where this design uses the first observation group (Pretest), the sample used is 40 people in the group Lecture method, and goup leaflet. The results of the T-test showed that the post-test knowledge of the lecture method was 11.87 and the post-test knowledge of the leaflet method was 10.47 where the lecture method was more effective in increasing the knowledge of respondents about choosing contraceptives, the attitude test of the lecture method was 39.33 and the post-test attitude. leaflet method is 31.53 where the lecture method is more effective in increasing the knowledge of respondents about the choice of contraceptives,. The conclusion is that there is a relationship between knowledge, attitudes, and actions pretest and posttest after being given intervenes with lecture and leaflet methods. Suggestions are expected that good cooperation in order to achieve effective decision-making begins with the BKKBN which provides socialization to health workers on contraceptives